PERAN KEPEMILIKAN ASING DALAM MEMODERASI PENGARUH KINERJA KEUANGAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Agusti, Orriyana; Tjahjono, Achmad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The aim of this study is to evaluate the moderating impact of foreign ownership on the relationship between capital structure and financial performance on firm value. The relationship between capital structure and financial performance on firm value. The research subjects were 625 Fast - Moving Consumer Goods Business (FMCG) companies registered (on) the Indonesian Stock Exchange​ listed on the Indonesian Stock Exchange between 2018 and 2022. 2018 and 2022 were the research subjects. ​ The research sample of 25 companies was selected. through the use of purposive sampling. 25 companies were selected through the use of purposive sampling. For the analysis, financial reports obtained from www.idx.co.id were used as secondary data. Obtained from www.idx.co.id were used as secondary data. Linear regression analysis Multiple regression analysis is used in this research as a data analysis technique. capital, and financial performance all have a major impact on a company's value. Interestingly, it was found that foreign ownership, which functions as a moderating variable, amplifies the impact of capital structure and financial performance on firm.